Potensi Peningkatan Hasil Jagung Manis (Zea Mays Saccharata Sturt) Melalui Kombinasi Dosis Pupuk Nitrogen dan Kalium - Ida Aryani; Gamal Abdul Nasser; Dali Dali; Neni Marlina; Marlina Marlina; Khodijah Khodijah; Joni Ph Rompas; Ahid Zamroni (Journal on Education, 2023)
This study aims to obtain the right dosage of nitrogen and potassium fertilizers as well as the interaction between nitrogen and potassium in increasing the growth and yield of sweet corn (Zea mays var. saccharata). This study used a factorial randomized block design consisting of 2 treatment factors, namely nitrogen and potassium fertilizer treatment, with 3 replications. Factor I Nitrogen fertilizer treatment with the dose: N0: Without nitrogen fertilizer (control), N1: Nitrogen fertilizer 150 kg/ha Urea, N2: Nitrogen fertilizer 300 kg/ha Urea. Factor II Potassium Fertilizer : K0 : Without Potassium Fertilizer (control), KI : Potassium Fertilizer 200 kg/ha K2O, K2 : Potassium Fertilizer 300 kg/ha K2O. The parameters observed in this study were plant height (cm), cob length (cm), cob weight (grams), cob diameter (grams) and dry chestnut weight (grams). The results of the analysis of variance showed that the treatment of nitrogen fertilizers and potassium fertilizers had a significant to very significant effect on all observed variables. The interaction of nitrogen and potassium fertilizers had a significant effect on cob weight and had a very significant effect on plant height, cob diameter and dry matter weight and had no significant effect on cob length.